Gold nanocages for cancer detection and treatment. (October 2007) - Skrabalak, Sara E; Au, Leslie; Lu, Xianmao; Li, Xingde; Xia, Younan
Gold nanocages represent a novel class of biocompatible vectors with potential applications in drug delivery, tumor/tissue imaging and photothermal therapy. They are prepared through the galvanic-replacement reaction between Ag nanostructures and HAuCl4 . By controlling the amount of HAuCl4 added, we can tune the surface-plasmon resonance peaks of the Au nanocages into the near-infrared, where the attenuation of light by blood and soft tissue is relatively low. Here, we highlight recent advances in the synthesis and utilization of Au nanocages for cancer detection and treatment. We have tailored the optical properties of Au nanocages for use as contrast agents in optical coherence tomography and as transducers for the selective photothermal ablation of cancer cells. Our results show improved optical coherence tomography image contrast when Au nanocages are added to tissue phantoms as well as the selective photothermal destruction of breast cancer cells in vitro when immunotargeted Au nanocages are used.